The Meaning of Dabbah in Surah Ash-Shu'ara 29: An Astrobiological Approach - Erwanto, Dian; Azizah, Nur; Zuhroh, Naila Izzatuz; Maulidah, Dewi; Faidah, Faidah (Noor: Journal of Islamic Studies, 2025)
This research attempts to prove the truth of the Quran with scientific facts based on the meaning of "dabbah" in Surah Ash-Shura 29, placing it within the scientific dialog of astrobiology. This is done by understanding the meaning of the interpretation and then linking it to exoplanet aspects and Unidentified Aerial Phenomena (UAP) phenomena. This research employs analytical interpretation methodology to examine the literal meaning, as well as the scientific interpretation approach to explore the relevance of the verses to contemporary knowledge. It contributes to scientific interpretation as an epistemological bridge between revelation and science, and offers a relevant interpretation framework for the development of contemporary Islamic studies. The study results indicate that classical commentators interpreted "dabbah" as a creature that moves on the surface of the earth, but modern science has expanded the horizons of interpretation thru the discovery of exoplanets in habitable zones and scientific studies of unexplained atmospheric phenomena. The integration of the two shows that the term "dabbah" does not only have a biological-literal meaning, but can also be read as a reflection of the cosmos on the possibility of extraterrestrial life.